Democratic community initiatives: the case of overscheduled children - Anderson, Jared R.; Doherty, William J. (My University, 2013)
We describe a democratic citizen model of community organizing for mobilizing and partnering with families, using the overscheduling of children as a case example. We provide an overview of the growing body of research on this aspect of family time, describe the difference between a citizen model and program models for working with families, give two examples of community initiatives initiated by family professionals, describe next steps for evaluating this community organizing model, and offer implications for family professionals.
Keywords: Family time; Community initiatives; Community; Evaluation; Overscheduled children